Sistem Pendukung Keputusan Pemilihan PMR Terbaik Tingkat Pelajar Menerapkan Metode EXPROM II - Tamba, Srira Ayu (TIN: Terapan Informatika Nusantara, 2021)
In the current era, helping behavior among the community or schools is considered lacking and even rarely done. The younger generation must have a character that reflects the nation's own personality, namely an attitude of caring, helping and having a human spirit. In general, teenagers spend a lot of time doing things that are not useful. To overcome the above problems, the Indonesian Red Cross (PMI) conducted an election for the Youth Red Cross (PMR) in order to foster an attitude of helping. However, the election effort is still subjective and there is no system that helps in the process of selecting the Youth Red Cross to be more accurate. To overcome these problems, it is necessary to build an application of the Youth Red Cross Election Decision Support System (PMR) using the Exprom II method so that it helps in the assessment process to be more accurate and the decisions that are determined are valid and satisfactory.